Adaptation a scale for teachers’ perceptions of the applications of scientific process skills: A study of validity and reliability - (:unkn) unknown (Sakarya University, 2016)
Today one of the main purposes of science education is to educate individuals to use scientific process skills. Individuals who grow in this context can be good citizens who knows the requirements of the age, questioning, investigating and able to establish a connection with daily life. In addition, while teaching science, the aim is not only to teach the concepts but also educate the students to solve the problems they face with throught their life, in scientific ways, and to manage to look through the scientisits’ eyes to the phenomena and the World. By providing these skills, it is mportant to know teachers’ perceptions of the applications of these skills. Literature show that there are limited valid and reliable instruments which evaluate teachers’ scientific process who teach science. From this point, in this study, the scale for teachers’ perceptions of the application of scientific process skills developed by Rambuda and Fraser (2004) was adapted. The adaptation process was performed in three different universities. The sample consisted of preservice teachers in three educational faculties. The scale consisted of 22 items using 4 point Likert Scale. The scale was applied to 686 preservice teachers in teacher training programme during 2014-2015 academic year. To test the language equivalance, English and Turkish versions of the scale was applied to 58 students in English teacher training programme and positive and significant correlations were identified. To determine construct validity of the scale, exploratory and confirmatory factor analysis were conducted. Results of exploratory factor analysis showed that the scale consisted of 2 dimensions: Basic science process skills and integrated science process skills. The valus of factor loadings varied within the range of,46-,78. The inner consistency coefficient for reliability was calculated to be, 91. The ciriterian validity results showed that the scale is suitable for the purpos. The result of confirmatory factor analysis showed that indices were found at an acceptable level and determined that the scale was relevant to the real data. The findings of the study identified that the teachers’ perceptions of the applications of scientific process skills scale is valid and reliable assessment tool. © The Turkish Online Journal of Educational Technology.
Keywords: Adaptation of scale; Reliability; Scale for application of scientific process skills; Validity